THEOPHYLLINE AND ACEBROPHYLLINE IN MILD BRONCHIAL ASTHMA: A COMPARATIVE STUDY OF EFFICACY AND SAFETY - DR.C.SARAVANAKUMAR; DR.VIJAYALAKSHMI; DR.PARAMESWARI (International Journal of Pharma and Bio Sciences, 2014)
To compare the efficacy and tolerability of Theophylline and Acebrophylline in mild persistent asthma.A randomized, open, parallel clinical study was conducted on 100 patients of mild persistent asthma. After baseline assessments, Theophylline was prescribed to 50 patients and Acebrophylline to another 50 for 4 weeks. The efficacy variables were change in asthma symptom scoring and pulmonary function test. At followup, the patients were re-evaluated and analyzed by statistical tools.The mean peak expiratory flow rate before and after therapy in Theophylline group was 202.6±41.6 and 222±45.1 ml respectively and in Acebrophylline group 183.3±40.8 and 237.3±47.5 ml respectively. The mean FEV1 before and after therapy in Theophylline group was 1.73±0.75 and 1.88±0 ml respectively and in Acebrophylline group 1.65±0.73 and 2.26±0.73 ml respectively. PEFR and FEV1, Cough scoring and sputum quantity was improved significantly in Acebrophylline group than Theophylline group. Side effects were significantly low in Acebrophylline than Theophylline group. Acebrophylline was found to be superior to Theophylline in terms of efficacy and tolerability in patients with mild bronchial asthma as evidenced by subjective and objective means.Acebrophylline was found to be superior compared to Theophylline in mild persistent asthma.